Study guides

☆☆

Q: 3ab plus 7ab-12ab equals

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

3ab + 3ac + 2b2 + 2bc = 3a(b + c) + 2b(b + c) = (3a + 2b)(b + c)

(3b - 1)(a - b)

2a-3ab = -1

(a+b)3=a3+b3+3ab(a+b) a3+b3=(a+b)3-3ab(a+b) a3+b3=(a+b)(a2-ab+b2)

5ab-2ab+4a-b+5b = 3ab+4a+4b

Related questions

12ab+3ab=15ab

a = 1

(a+b)(3b+1)

3ab + 3ac + 2b2 + 2bc = 3a(b + c) + 2b(b + c) = (3a + 2b)(b + c)

(3ab*pi)

Provided multiplication is commutative, it is 8ab.

(3b - 1)(a - b)

It is an algebraic expression because it has no equality sign.

3a(b+c)+2b(b+c)

2a-3ab = -1

6

(3a - 2c)(b - d)

People also asked